Glucose-6-phosphate dehydrogenase activity in male premature and term neonates. Issue 6 (21st October 2004) - Mesner, O; Hammerman, C; Goldschmidt, D; Rudensky, B; Bader, D; Kaplan, M
Abstract : Background: Glucose-6-phosphate dehydrogenase (G6PD) activity is higher in term neonates than in adults. Some studies have suggested that activity may be even higher in preterm infants. Objectives: To determine if G6PD activity is higher in preterm than term neonates, and whether higher activity would interfere with diagnosis of G6PD deficiency in premature infants. Methods: G6PD activity was determined in the first 48 hours after delivery in male premature, term, and near term infants. G6PD deficient neonates were separated, and the remaining premature infants compared with healthy, male, G6PD normal, near term and term neonates. Results: Ninety four premature infants (mean (SD) gestational age 31.9 (3.8) weeks (range 23–36)) were studied. In four, G6PD activity was 0.8–1.8 U/g haemoglobin (Hb), which is clearly in the deficient range with no overlap into the normal range. G6PD activity in the remaining premature infants was significantly higher than in 24 near term and term neonates (gestational age ⩾ 37 weeks) (14.2 (4.6) v 12.0 (3.8) U/g Hb). Further analysis showed that significance was limited to those born between 29 and 32 weeks gestation, in which group G6PD activity was significantly higher than in those born before 29 weeks gestation, at 33–36 weeks gestation, and ⩾ 37 weeks gestation. Conclusions: G6PD activity is higher in premature infants born between 29 and 32 weeks gestation than in term neonates. This did not interfere with diagnosis of G6PD deficiency.